2008
DOI: 10.1007/s11936-008-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomarkers to develop treatment strategies for atherosclerosis

Abstract: This review focuses on the recent progress in and future prospects for the widened use of biomarkers of inflammation to modify lipid treatment goals in individuals assessed according to traditional risk factors to be at moderate or higher risk for clinical cardiovascular disease events. Elevated blood levels of high-sensitivity C-reactive protein or lipoprotein-associated phospholipase A(2) independently predict increased risk after adjustment for an individual's clinical risk status. When elevated individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…In general, the association between AF and inflammation is well established, and several prior studies have documented the relationship with CRP 3,4,22–30 . Importantly, AF also increases other inflammatory markers as well, including complement (C3, C4), prothrombin fragments, and interleukin‐6 25,26 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the association between AF and inflammation is well established, and several prior studies have documented the relationship with CRP 3,4,22–30 . Importantly, AF also increases other inflammatory markers as well, including complement (C3, C4), prothrombin fragments, and interleukin‐6 25,26 .…”
Section: Discussionmentioning
confidence: 97%
“…In our study, AF was associated with the increased mean CRP level across all levels of CHADS2 scores, which suggests that the association between AF and inflammation is not based on comorbidities alone. These data have clinical importance as CRP and other inflammatory marker elevations in patients with AF have been associated with worse outcomes such as death, stroke, and arrhythmia recurrence after cardioversion 27–30 . Furthermore, these data assist in defining AF as a risk factor in addition to a risk marker of other diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Supklinička faza ateroskleroze je oštećenje endotela i postepeno difuzno zadebljanje IMK 14,15,[34][35][36][37][38][39][40] . Informacija o ovom procesu se ne može dobiti angiografijom ili nuklearnom magnetnom rezonancom (MRI) 35,36 .…”
Section: Diskusijaunclassified
“…Informacija o ovom procesu se ne može dobiti angiografijom ili nuklearnom magnetnom rezonancom (MRI) 35,36 . To je neinvazivno i moćno sredstvo u dijagnostikovanju, merenju i praćenju procesa ateroskleroze 2,7,12,15,26,34,37,[41][42][43][44] . To je neinvazivno i moćno sredstvo u dijagnostikovanju, merenju i praćenju procesa ateroskleroze 2,7,12,15,26,34,37,[41][42][43][44] .…”
Section: Diskusijaunclassified
“…Observational and epidemiologic studies demonstrated that elevated levels of sPLA 2 [29] or Lp-PLA 2 [30] predict increased risk of CHD events and stroke, with Lp-PLA 2 predicting risk independently of CRP [31]. Important evidence supporting a pathophysiologic role for Lp-PLA 2 in atherosclerosis progression was presented by Lavi et al [32] in work demonstrating that in subjects with nonobstructive atherosclerosis detected by intravascular ultrasound, the coronary circulation becomes a net producer of Lp-PLA 2 and lyso-PC.…”
Section: Phospholipases a 2 : Spla 2 And Lp-plamentioning
confidence: 99%